2014
DOI: 10.1902/jop.2013.130498
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Areca Nut Extract on Expression of Complement Receptors and Fc Receptors in Human Neutrophils

Abstract: ANE inhibits the complement- and IgG-mediated neutrophil phagocytosis that may result from reduction of the expression of complement receptors, Fc receptors, and F-actin formation after ANE treatment. The findings suggest that areca nut chewing may jeopardize the defensive functions of neutrophils and affect periodontal health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…For example, calcium hydroxide (slaked lime) was present in all the chewed products, and calcium hydroxide is a strong alkali that can irritate the oral mucosa (Dunham, Muir, & Hamner, ; Javed, Chotai, Mehmood, & Almas, ). Another common element observed in the chewing products was the areca nut, which has been demonstrated to alter gingival keratinocytes and fibroblasts (Chang et al., ; Jeng et al., ) and modify the antimicrobial function of neutrophils (Lee et al., ). Furthermore, the effect of tobacco used locally (chewed tobacco) causes hyperaemia in the gingiva (Mavropoulos, Aars, & Brodin, ) and increases the levels of periodontitis and gingival bleeding (Amarasena et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, calcium hydroxide (slaked lime) was present in all the chewed products, and calcium hydroxide is a strong alkali that can irritate the oral mucosa (Dunham, Muir, & Hamner, ; Javed, Chotai, Mehmood, & Almas, ). Another common element observed in the chewing products was the areca nut, which has been demonstrated to alter gingival keratinocytes and fibroblasts (Chang et al., ; Jeng et al., ) and modify the antimicrobial function of neutrophils (Lee et al., ). Furthermore, the effect of tobacco used locally (chewed tobacco) causes hyperaemia in the gingiva (Mavropoulos, Aars, & Brodin, ) and increases the levels of periodontitis and gingival bleeding (Amarasena et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the dendritic cell (DC) population in pre-malignant and malignant oral lesions with higher grades ( Pellicioli et al, 2017 ), may promote malignancy through immune evasion. Several studies have shown the downregulation of immune response among those who chew areca nut ( Wang et al, 2011 ; Wang et al, 2012 ; Chang et al, 2014 ; Lee et al, 2014 ). Areca nut extract (ANE) inhibits the differentiation and function of DCs ( Wang et al, 2012 ; Lee et al, 2014 ).…”
Section: Capsaicin As An Anticarcinogenic Agentmentioning
confidence: 99%
“…Several studies have shown the downregulation of immune response among those who chew areca nut ( Wang et al, 2011 ; Wang et al, 2012 ; Chang et al, 2014 ; Lee et al, 2014 ). Areca nut extract (ANE) inhibits the differentiation and function of DCs ( Wang et al, 2012 ; Lee et al, 2014 ). Furthermore, augmentation of myeloid-derived suppressor cells (MDSC) via continued areca nut use fosters malignancy through auxiliary downregulation of the immune response ( Dolcetti et al, 2010 ; Wang et al, 2011 ).…”
Section: Capsaicin As An Anticarcinogenic Agentmentioning
confidence: 99%
“…The aqueous extract of dried ripe Areca catechu nuts reduces the levels of Fc γ Rs and CRs expression in human neutrophils and impairs the neutrophil phagocytic ability towards complement- and IgG-opsonized microspheres [ 148 ]. The combination of ascorbate (vitamin C) and tocopherol (vitamin E) inhibits ROS generation by human neutrophils stimulated via Fc γ R with IgG-opsonized Staphylococcus aureus and Fusobacterium nucleatum [ 158 ].…”
Section: The Use Of Natural Products As Therapeutic Adjuvants To Tmentioning
confidence: 99%